Button power - Carter, Christen; Hake, Theodore L. (Princeton Architectural Press, 2021)
"A collection of more than 2,000 colorful and artistic pin-back buttons, forming a people's history of American culture and politics that focuses on a range of subjects: advertising, arts and entertainment, historical events, movements and causes, humor, nature, celebrated personalities and organizations, geographical features, sports, transportation, wars and anti-war movements"--